A Rare Case of Lemierre-Like Syndrome: A Case Report and Literature Review. (1st April 2018) - Ibrahim, Judy; Noureddin, Muhammad Bassel; Lootah, Ali; Al Khalidi, Aisha; Ghatasheh, Ghassan; Al Tatari, Hossam
Abstract : Lemierre's syndrome (LS) is a serious rare complication of oropharyngeal infections. It is characterized by thrombosis of internal jugular vein that rapidly progresses into sepsis and is typically caused by anaerobes. Most of the reported cases have been linked to Fusobacterium necrophorum ; however, there are a handful of reported cases due to aerobes. It is primarily the disease of healthy young adults and can present in school-aged children. The early recognition and treatment of this complication results in resolution of the illness; nevertheless, there have been some concerns about chronic venous insufficiency as a long-term complication. We report a case of a 6-year-old boy, who presented with fever and headache with a history of sore throat. His blood culture was positive for group A Streptococcus (GAS) and was subsequently found to have internal jugular vein, sigmoid, and transverse sinus vein thrombosis.